Pemahaman Siswa Kelas VIII Terhadap Materi Lingkaran dalam Bentuk Komik Digital - Utari, Hani (Sekolah Pascasarjana Institut Kesenian Jakarta, 2024)
This study aims to determine students’ comprehension of the development of learning companion media using HOTS Circle questions in the form of digital comics for junior high school students and to improve the quality of teaching materials in schools. This research is the development of learning media using Research and Development (RnD) and Focus Group Discussion (FGD) methods. The product of this research is in the form of digital comic learning media which has been uploaded to the webtoon application and has now been re-uploaded to owltoon.site. This comic has 8 episodes of stories and has a science fiction genre about circle material on mathematics in everyday life. The comic entitled Building Math tells the story of three students who receive a mysterious letter containing an invitation to visit an address. The address leads to an uninhabited building. Every visitor who has entered the building will not be able to get out again, unless they can complete the challenges that are on each floor of the building. Research shows that the developed media is rated by experts in the “good” or “valid” category on the Likert scale. Through the Focus Group Discussion (FGD) that has been conducted it was found that Building Math comics were effective as an attraction for students in the circle learning process in class._____________________________________________________Penelitian ini bertujuan untuk mengetahui pemahaman siswa terhadap pengembangan media pendamping pembelajaran menggunakan soal HOTS Lingkaran dalam bentuk komik digital untuk siswa tingkat SMP dan meningkatkan kualitas bahan ajar di sekolah. Penelitian ini merupakan pengembangan media pembelajaran dengan metode Research and Development (RnD) dan Focus Group Discussion (FGD). Produk penelitian ini berupa media pembelajaran komik digital yang sudah pernah di upload pada aplikasi webtoon dan saat ini sudah di upload 69 kembali di owl toon.site. Komik ini memiliki 8 episode cerita dan memiliki genre fiksi ilmiah tentang materi lingkaran pada matematika dalam kehidupan sehari-hari. Komik berjudul Building Math ini menceritakan tiga orang siswa yang mendapatkan surat misterius yang berisikan undangan untuk mendatangi sebuah alamat. Alamat itu mengarah pada sebuah gedung yang tak berpenghuni. Setiap pengunjung yang sudah masuk pada gedung itu tidak akan bisa keluar lagi, kecuali dapat menyelesaikan tantangan yang berada pada setiap tahap lantai gedung itu. Penelitian menunjukkan bahwa media yang dikembangkan ini mendapatkan penilaian dari para ahli dengan kategori “baik” atau “valid” dalam skala likert. Melalui Focus Group Discussion (FGD) yang telah dilakukan ditemukan bahwa komik Building Math efektif sebagai daya tarik siswa dalam proses pembelajaran Lingkaran di kelas.